Sacred Forests, Sacred Nation: The Shinto Environmentalist Paradigm and the Rediscovery of "Chinju no Mori" - Rots, Aike P. (Japanese journal of religious studies, 2015)
In June 2014, a large international and interreligious conference took place at the shrines of Ise, Shinto s most sacred site. Devoted to the topic of religion and environmental sustainability, the event constitutes a clear example of the global trend to reinterpret religious beliefs and practices in the light of contemporary environmental concerns, and to redefine sacred sites as ecological resources in need of conservation. One religious tradition that has been reconceptualized as an environmentally friendly tradition, allegedly characterized by centuries -old nature worship, is Shinto. This article outlines the development and characteristics of this "Shinto environmentalist paradigm," which has led to the transformation of Shinto identities and shrine practices, and analyzes one of its core concepts: chinju no mori (sacred shrine forests). In addition, the article gives some concrete and representative examples of shrine-based conservation projects, and discusses some of the ways in which the Shinto environmentalist paradigm is adapted and negotiated by local actors.